Evaluation of Hand Hygiene Practices and Educational Interventions Among Indonesian Nursing Students: An Analysis Using ATP Wipe Tests and Hand Hygiene Checkers - Sato, Mayumi; Syahrul; Susanto, Tantut; Fithria; Hokama, Naoki; Saito, Ruka; Djaya, Andi Muhammad Fiqri Muslih; Sugimoto, Hiroshi (Journal of Rural Community Nursing Practice, 2025)
Background: Infectious diseases, including dengue fever and waterborne infections, remain major public health concerns in Indonesia. Hand hygiene is essential for reducing healthcare-associated infections; however, nursing students often fail to practice it effectively despite having sufficient knowledge. Purpose: The present study evaluated the implementation of hand hygiene among Indonesian nursing students, assessed their adherence to the “Five Moments for Hand Hygiene” during clinical training, and examined the necessity for educational improvements using a hand hygiene checker and ATP swab testing. Methods: A cross-sectional study was conducted among nursing students from three national universities in Indonesia. Data were collected through a questionnaire survey on hand hygiene knowledge and practices, self-reported adherence to the 'Five Moments for Hand Hygiene' during clinical training, and an objective evaluation using a hand hygiene checker and ATP swab testing. Results: The majority of students understood hand hygiene techniques; however, 70% failed to meet the WHO recommended handwashing duration. Over 30% of students found it challenging to perform hand hygiene before patient contact and after touching objects in the patient’s surroundings. The hand hygiene checker revealed residual contamination on the nails and fingertips, while ATP swab testing showed that 60% of students did not meet the standard threshold. Conclusions: Despite their knowledge, nursing students face challenges in implementing the proper hand hygiene practices. Knowledge alone is insufficient; practical education with visual and numerical feedback is essential. Training with hand hygiene checkers and ATP swab testing can improve self-assessment skills and enhance adherence to hand hygiene protocols.